The Role of Natural Products in Antiviral Drug Discovery: Insights into Mechanisms and Therapeutic Potential - Mohammad Adham (International Journal of Virus Studies, 2024)
Drug discovery has always relied heavily on natural sources, especially when it comes to creating antiviral medications. This review explores the therapeutic potential of various natural products, including plant extracts, marine compounds, and microbial metabolites, in the fight against viral infections. We examine the mechanisms of action by which these natural compounds exert their antiviral effects, including direct inhibition of viral replication, modulation of host immune responses, and interference with viral entry and assembly. Additionally, we highlight the challenges in translating natural product research into clinical applications, such as bioavailability, stability, and the need for further pharmacological studies. Modern methods of extraction and synthesis are also covered, with a focus on how they can improve the effectiveness of natural products. As the global landscape of viral diseases continues to evolve, the importance of exploring and integrating natural compounds into antiviral strategies cannot be overstated .This review aims to provide a comprehensive overview of the current trends in antiviral drug discovery from natural sources and to underscore the potential for integrating traditional knowledge with modern pharmacological approaches.
Keywords: Antiviral Drug Discovery; Marine Compounds; Mechanisms of Action; Microbial metabolites; Natural Products; Pharmacological Studies; Plant extracts; bioavailability; therapeutic potential; viral infections